2020
DOI: 10.1021/acs.analchem.9b05712
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Label-Free Thermal Stability Assay for Protein Denaturation and Protein–Ligand Interaction Studies

Abstract: In modern biochemistry, protein stability and ligand interactions are of high interest. These properties are often studied with methods requiring labeled biomolecules, as the existing methods utilizing luminescent external probes suffer from low sensitivity. Currently available label-free technologies, e.g., thermal shift assays, circular dichroism, and differential scanning calorimetry, enable studies on protein unfolding and protein–ligand interactions (PLI). Unfortunately, the required micromolar protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…Interactions between proteins are a fundamental part of correct cellular functionality, and impaired interactions may lead to various disease states. We have previously developed a label-free method for the detection of protein stability and PLIs, 27 which we now apply for PPI monitoring. The protein probe technique is based on a negatively charged Eu 3+ chelate-labeled peptide (Eu 3+ probe) used to measure protein structural changes, such as an increased surface area and exposed hydrophobic regions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interactions between proteins are a fundamental part of correct cellular functionality, and impaired interactions may lead to various disease states. We have previously developed a label-free method for the detection of protein stability and PLIs, 27 which we now apply for PPI monitoring. The protein probe technique is based on a negatively charged Eu 3+ chelate-labeled peptide (Eu 3+ probe) used to measure protein structural changes, such as an increased surface area and exposed hydrophobic regions.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that an increase in the TRL signal is observed when a heated and denatured protein sample is monitored with the protein probe method, and we expected to measure an improved detectability with PPIs. 27 In all assays, the reactions are performed in biologically relevant buffers at RT, and thereafter the protein complex is heated to a given temperature. For the detection, the protein solution is reverted to RT by adding the protein probe solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Eu-probe was purified as described before, [31] and the concentration was determined using the DELFIA technique and a commercial EuCl 3 standard from PerkinElmer Life and Analytical Sciences, Wallac (Turku, Finland). The protein substrates, recombinant pertussis toxin (PTX), G protein alpha I subunit (Gαi) [33], human Ras GTPase-activating protein 1 (p120GAP) [34], wild type Kirsten RAt Sarcoma virus (KRAS, 2-188), human son of sevenless SOS1 catalytic domain (SOS cat , 564-1048) [35], and eukaryotic initiation factor 4A1 (eIF4A1) [32] were kind gifts from our collaborators. Malate dehydrogenase (MDH) was purchased from Roche (Basel, Switzerland).…”
Section: Materials Instrumentation and Assay Buffersmentioning
confidence: 99%
“…In addition, our Protein-Probe method requires only a fraction of the sample compared to other introduced methods, and it is also suitable for protein stability monitoring, giving additional information when assayed with thermal ramping. 35 , 36 Here, we used the Protein-Probe in a proof-of-principle study to monitor a panel of monoclonal antibodies (mAbs) and their heat- or pH-induced aggregation (RT measurements), and also stability in thermal ramping. Both monitored parameters – aggregation behavior and thermal stability – can give important information on therapeutic mAbs.…”
Section: Introductionmentioning
confidence: 99%